The world around you - Asimov's, Isaac 02/01/1920-06/04/1992 (New York : Lancer, 1966)
A scientific description of what the earth is made of.
This edition is for readers for whom English is a second language. It can be anyone whos has learned 2,000 words of english.
Keywords: Quimica; Atomos; Tabla Periodica; Minerales